Iraqi Parilamentary Elections after 2003 Between Theory and Practice - Al-Naeb, Ehsan Abdulhadi (Journal of Legal and Political Studies, 2020)
This research theoretically deals with the aim, importance and forms of elections, and also with the electoral systems and its various types and goals. Experiences In the last decades proved that the process of election and the kind of electoral systems have significant influence, especially in the period of a democratic transition. It can either reduce social conflicts, or it can escalate social conflict inside a society. In the practical side, this study has shed light on elections in Iraq that have implemented in a context in which it has faced political and legal challenges. Most obvious challenges were the need of the implementation of international criteria such as credibility, integrity and transparency. In addition to the need to design an electoral system which can suit the political, social, cultural and economic contexts, and finding a better way to distribute the representative seats. This will allow representative bodies (parliament) to give more voice to the majority of the ingredients, and also performs its duties more functionally.
Keywords: Iraq; Elections; Forms of elections; Electoral Systems; Democracy; parliament